Discordant genotyping results using DNA isolated from anti‐doping control urine samples. Issue 7 (4th November 2016) - Choong, Eva; Schulze, Jenny J; Ericsson, Magnus; Rane, Anders; Ekström, Lena
Abstract : The UGT2B17 gene deletion polymorphism is known to correlate to urinary concentration of testosterone‐glucuronide and hence this genotype exerts a large impact on the testosterone/epitestosterone (T/E) ratio, a biomarker for testosterone doping. The objective of this study was to assess if DNA isolated from athletes' urine samples (n = 713) obtained in routine doping controls could be targeted for genotyping analysis for future integration in the athlete's passport. A control population (n = 21) including both urine and blood DNA was used for genotyping concordance test. Another aim was to study a large group (n = 596) of authentic elite athletes in respect of urinary steroid profile in relation to genetic variation. First we found that the genotype results when using urine‐derived DNA did not correlate sufficiently with the genotype obtained from whole blood DNA. Secondly we found males with one or two UGT2B17 alleles had higher T/E (mean 1.63 ± 0.93) than females (mean 1.28 ± 1.08), p˂0.001. Unexpectedly, we found that several male del/del athletes in power sports had a T/E ˃1. If men in power sport exert a different urinary steroid profile needs to be further investigated. The other polymorphisms investigated in the CYP17A1, UGT2B7 and UGT2B15 genes did not show any associations with testosterone and epitestosterone concentrations. Our results show that genotyping using urine samples according to our method is not useful in an anti‐doping setting. Instead, it is of importance for the anti‐doping test programs to include baseline values in the ABP to minimize any putative impact of genotype. Copyright © 2016 John Wiley & Sons, Ltd. Abstract : Genotype analysis using DNA isolated from urine may give false results, indicating that this approach is not useful in an anti‐doping setting. Some athletes devoid of the UGT2B17 gene may have a T/E > 1. This appears to be more common among men in power sports.